Qualidade dos dados clínicos oriundos de prontuários eletrônicos segundo profissionais de tecnologia da informação em saúde e lideranças médicas especialistas em TI - Rocha Junior, José Aldir da (2020)
The electronic medical record should offer a list of problems that indicate the patient's current and past problems; be able to measure the patient's functional and health status; to be able to document clinical reasoning in diagnoses, conclusions and in the selection of therapeutic interventions; be a longitudinal record covering the entire life of the patient, linking all data from previous consultations and consultations; guarantee confidentiality and privacy and support the clinical and administrative audit processes; offer continuous access to authorized users; allow simultaneous and customized viewing of patient data by professionals, departments and companies; support online access to local and remote information resources; facilitate the solution of clinical problems by providing analysis and decision tools; support data entry directly by the doctor; support professionals in cost management and control to improve quality; have flexibility to support the incorporation of existing and future needs of clinical specialties. From this perspective of the electronic medical record, it is clear the need to incorporate technology into the electronic medical record so that it is able to meet these prerequisites and, more than that, can evolve to the new needs that arise with the advancement of the information. In this context, the general objective of this research was to highlight the current structural and functional elements of the Electronic Patient Record and their relationships and limitations with the Electronic Health Record and Telemedicine. This is qualitative health research, which opted for data collection through semi-structured interviews and used Content Analysis to interpret the data. First, it was evaluated how respondents define the structural elements of electronic medical records, considering that these solutions are one of the main instruments of assistance for clinical practice. The second part of the results, examines the functional elements of electronic medical records, in how the interviewees perceive the adherence of these systems to the daily life of doctors, nurses and other healthcare professionals; how they understand the dynamics of handling the data they produce and consult; what impacts they have on clinical efficiency and patient safety. Electronic patient records are a source of clinical information of great relevance to Health and responsible for significant advances since its adoption. However, even though they are noticeably improved, these solutions remain tied to a functioning model that does not favor a versatile production of reliable data for the second leap that they need to take towards Digital Health - a reality that was imposed with the pandemic of COVID- 19 -, where semantic interoperability will optimize efforts and reduce waste. When conducting interviews with technology professionals involved in health information, whose script was prepared from the structural and functional perspectives of electronic medical records, it became evident that the software industry will not be the locomotive of this change, as it is a reflection of the expectations of its clients, still immersed in remuneration issues to the detriment of the needs of care practice, one of the main causes of emotional exhaustion that has affected medical professionals in recent years. The result of this analysis demonstrated that these solutions have a path of improvement to go, but they need to be pulled by important discussions in Health. The preponderance of this approach in hospitals and operators, guided the priorities and investments of the software industry to enable functionalities focused on controls who distance themselves from assistance, establishing a vicious circle that converts into excessive screens and clicks.